What Is the Role of AI in Stroke Rehabilitation? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2017)
Stroke remains a leading cause of long-term disability worldwide, necessitating innovative and effective rehabilitation strategies. In recent years, Artifici...
Keywords: AI in Rehabilitation Medicine; Stroke; Rehabilitation; Artificial Intelligence; Machine Learning; Deep Learning; Healthcare